A Study of the Oral Toxicity of Calcium Chloride in Dairy Cows - Mathieu, L. G. (1966)
The effects of oral administration of calcium chloride solutions to dairy cows were studied. When a 0.3 per cent solution was given ad libitum, and as the sole source of water for a period of 75 days, we observed no significant changes in feed consumption, body weight or milk production. The average daily water intake was increased by approximately 20 per cent, and signs of slight gastro-intestinal irritation were seen. No major changes in blood hemoglobin levels, hematocrits, total and differential white cell counts or thrombocyte numbers could be attributed to the treatment. We observed no significant effect on the serum calcium, chloride, magnesium, potassium, or sodium content. The level of inorganic phosphate in the serum rose to higher, but still normal values. During the entire experiment the urine pH was abnormally acid for dairy cows. Electrocardiograms were taken after 45 days of calcium chloride administration, and they appeared normal. When 0.1 and 0.2 per cent solutions were given as the sole source of water for a period of 81 days, the cows remained in good condition, and we observed no changes in appetite, body weight or milk production. In general, dairy cows will refuse to drink calcium chloride solutions when the concentration exceeds 0.5 per cent, even when they have been deprived of water for 18-24 hours. On the other hand, since the administration of lower concentrations for periods of 75 and 81 days did not cause any clinical sign of disease, it seems that on farms where more than one source of water are usually available, poisoning of dairy cattle by calcium chloride in solution is quite unlikely.